Conceptualization of the Integrated Islamic Religious Education Curriculum: A Literature Study at Imam Hatip Schools Turkey and MAN Insan Cendekia Indonesia - M. Fajar Sidik; Vrisko Putra Vachruddin; Evi Fatimatur Rusydiyah; Ani Setya Pertiwi; Mugthi Alintya Darmawan (Jurnal Pendidikan Agama Islam, 2024)
Purpose – The authors aim to compare Imam Hatip School (IHS) with MAN Insan Cendekia (MAN IC), two Islamic educational institutions that have successfully implemented an Islamic religious education curriculum integrated with general science. Design/methods/approach – This study used a literature review research method that examined several sources and government documents in three languages. The data collection technique was conducted by extracting and evaluating information in articles that meet the inclusion criteria. Once extracted and evaluated, the authors analyzed and interpreted the data. Findings – The integrated curriculum of Islamic education in IHSs aims to anticipate extreme, radical understandings and rejection of the state that implements the secular system. It will form the nature and attitude of tolerance among fellow citizens, allowing it to reduce social conflicts. The IHSs has implemented the integrated Islamic education curriculum by adopting a modern education system. The implementation of the integrated PAI curriculum at MAN IC aims to eliminate the paradigm and praxis of the dichotomy of science. MAN IC adopts an integrated Islamic religious education curriculum based on the traditional Islamic system with a mandatory policy to stay at a dorm for students, where religious activities are more emphasized when students are in the dormitory. Research implications/limitations – This research still has limitations due to a limited literature review and verification study in closed terms on our respondent informants. Therefore, further research is required to deepen the examination in this study. Originality/value – The findings in this study have included the aspects of policy, strategy, content or material development, and the implementation results of the integrated PAI curriculum in the two institutions. Those aspects build a socio-cultural identity, allowing it to develop the school in the realm of progress and achievement. The expectation is that this research can become an example for the development of Islamic Education Institutions in integrating the PAI curriculum.